2010
DOI: 10.1111/j.1365-294x.2010.04982.x
|View full text |Cite
|
Sign up to set email alerts
|

One haploid parent contributes 100% of the gene pool for a widespread species in northwest North America

Abstract: The monoicous peatmoss Sphagnum subnitens has a tripartite distribution that includes disjunct population systems in Europe (including the Azores), northwestern North America and New Zealand. Regional genetic diversity was highest in European S. subnitens but in northwestern North America, a single microsatellite-based multilocus haploid genotype was detected across 16 sites ranging from Coos County, Oregon, to Kavalga Island in the Western Aleutians (a distance of some 4115 km). Two multilocus haploid genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 83 publications
(98 reference statements)
4
55
0
Order By: Relevance
“…Microsatellite analysis has shown that other regional populations of Sphagnum have resulted from just one or two founders (Karlin et al, 2011a(Karlin et al, , 2012. Just one founder appears to have given rise to the regional population of the monoicous S. subnitens in north-western North America, with two founders apparently being associated with the South Island population of this species (Karlin et al, 2011a).…”
Section: Clonal Regional Populations?mentioning
confidence: 98%
See 2 more Smart Citations
“…Microsatellite analysis has shown that other regional populations of Sphagnum have resulted from just one or two founders (Karlin et al, 2011a(Karlin et al, , 2012. Just one founder appears to have given rise to the regional population of the monoicous S. subnitens in north-western North America, with two founders apparently being associated with the South Island population of this species (Karlin et al, 2011a).…”
Section: Clonal Regional Populations?mentioning
confidence: 98%
“…Just one founder appears to have given rise to the regional population of the monoicous S. subnitens in north-western North America, with two founders apparently being associated with the South Island population of this species (Karlin et al, 2011a). In both cases, long distance dispersal by spores produced by intragametophytic selfing and vegetative propagation at each site resulted in the rapid dispersal and establishment of S. subnitens on a regional basis.…”
Section: Clonal Regional Populations?mentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 100 per cent of the gene pool of Sphagnum subnitens in North America was contributed by one individual plant [56], and while this took place over 300 years as a natural process, it is likely to be achieved far more rapidly with human intervention.…”
Section: (A) Increased Expression Of Phenolic Inhibitorsmentioning
confidence: 99%
“…Sphagnum subfulvum mainly occur in boreal regions of North America and Europe, but also in temperate and sub-meridional regions in southern Europe at higher elevations and in arctic Greenland (McQueen and Andrus 2007). Sphagnum subnitens is found in most European countries (Daniels and Eddy 1990), along the Pacific coast of North America from Oregon to boreal parts of Alaska including the Aleutians (McQueen and Andrus 2007), and New Zealand (Karlin et al 2011). Thus, S. incundum, together with S. subfulvum, has a boreal to arctic distribution, while the other species are boreal to temperate.…”
Section: Discussionmentioning
confidence: 99%